Real Numbers, Sequences and Series - M T Nowak; W J Kaczor (Hyderabad, 2024)
We learn by doing. We learn mathematics by doing problems. And we learn more mathematics by doing more problems. If you want to hone your understanding of continuous and differentiable functions, this book contains hundreds of problems to help you do so. The emphasis here is on real functions of a single variable. Topics include: continuous functions, the intermediate value property, uniform continuity, mean value theorems, Taylors formula, convex functions, sequences and series of functions. The book is mainly geared toward students studying the basic principles of analysis.
English
Keywords: Mathematics